The ANALYSIS OF THE SPONTANEITY SPEECH IN SPEAKING ASSESSMENT AT INSTITUTION OF FOREIGN LANGUAGE DEVELOPMENT AL-YASINI PASURUAN - Lailil Nur Fitriani; Khodijah, Siti (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
Speaking is more than just creating and constructing sentences correctly and with proper grammar, but the ability to speak has a broad scope, such as in the fields of mechanics, functions, pragmatics, communication, and social interaction. To find out the students' ability, the teacher gives them a test. As an assessment, the teacher conducts a speaking test to find out how well students speak and their progress in learning. The speaking test is a procedure to measure students' speaking ability in which students are required to speak aloud, conveying their ideas, and then students are graded based on their speech. This research was conducted at LPBA Al-Yasini where the researchers focused on the scoring procedure for the spontaneity speech in assessing the students’ speaking skill. This research was descriptive-qualitative method. The result of the research was there are several aspect that used by LPBA to assess spontaneity speech, which are fluency, grammar, vocabulary, comprehension, pronunciation they are then divided into three categories, which are body language, delivery and content.